Faktor-Faktor Kunci Keberhasilan Pengembangan Kapasitas Organisasi di Era Digital - Firman Firman; Lusia Lestina Halawa; Mira Sukma; Evlin Limbong; Rika Sartika (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
Digital transformation has become a major driver of organizational change across sectors. However, many organizations still fail to build adequate capacity due to a lack of understanding of the critical success factors in the digital era. This study aims to identify and analyze key elements that influence the success of capacity development in organizations facing digital disruption. Using a descriptive qualitative approach, data were collected through literature reviews and case analyses of organizations that successfully implemented digital transformation. The findings indicate that success is determined by the synergy of four primary factors: transformational leadership, adaptive organizational culture, human resource competence, and technological readiness. These factors operate not in isolation but as a mutually reinforcing managerial ecosystem. Visionary leadership shapes innovative culture; supportive culture enhances HR capabilities; and competent HR facilitates optimal use of technology. This study contributes theoretically by offering an integrative and practical model that can serve as a strategic guide for organizations aiming to enhance their internal capacity sustainably in the face of digital complexity.